Work Incentives and the Probability of Leaving Unemployment in the Slovak Republic - Martina Lubyova; Jan C. van Ours (Tinbergen Institute, 1997)
The system of unemployment benefits and subsistence benefits in Slovakia has potentially largedisincentive effects with respect to the outflow from unemployment to a job. Especially low educatedunemployed and unemployed with young children are often faced with replacement ratios which areclose to 100%. We investigate whether the potential effects have an actual meaning. Using data fromsubsequent labour force surveys we analyse the (hazard) rates at which unemployed workers find jobs.We find no evidence of disincentive effects of the Slovak unemployment system.
Keywords: 330; Arbeitslosenversicherung; Öffentliche Sozialleistungen; Arbeitsangebot; Slowakei